THE WOMEN OF AGABAGAYA: EDUCATION AND POST‐DEVELOPMENT THEORY - Janzen, Melanie (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
This article describes a snapshot ethnography conducted in Uganda with the Agabagaya Women’s Group. The purpose of the study was to explore how women share knowledge among themselves to support their communities. Using post‐ development theory and Freire’s critical theory as a lens, I argue that although international development is often focused on women’s education, imposed develop‐ ment initiatives may actually hinder women’s ability to share meaningful knowledge. I conclude with a discussion of key points and how they relate to education within a context of development and within post‐development theory. Key words: international development, post‐development theory, women’s education, snapshot ethnography Cet article présente une brève étude ethnographique de l’Agabagaya Women’s Group de l’Ouganda. L’auteure analyse comment les femmes mettent leurs connaissances en commun au profit de leurs communautés. Utilisant la théorie du postdéveloppement et la théorie critique de Freire, elle soutient que, même si le développement international est souvent axé sur l’éducation des femmes, les initiatives de développe‐ ment imposé risquent d’entraver l’aptitude des femmes à partager des connaissances significatives. L’auteure termine en expliquant le lien entre ses résultats principaux et l’éducation dans le contexte du développement et à la lumière de la théorie du postdéveloppement. Mots clés : développement international, théorie du postdéveloppement, éducation africaine, ethnographie.